2023
DOI: 10.3390/gels9060454
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Hydrogel-Based Adsorbent Material for the Effective Removal of Diclofenac Sodium from Wastewater

Abstract: The removal of pharmaceutical contaminants from wastewater has gained considerable attention in recent years, particularly in the advancements of hydrogel-based adsorbents as a green solution for their ease of use, ease of modification, biodegradability, non-toxicity, environmental friendliness, and cost-effectiveness. This study focuses on the design of an efficient adsorbent hydrogel based on 1% chitosan, 40% polyethylene glycol 4000 (PEG4000), and 4% xanthan gum (referred to as CPX) for the removal of diclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…By swelling analysis demonstrated that the synthetized hydrogel is not dependent of pH. Results showed that the obtained hydrogel reached a adsorption capacity of 172.41 mg g −1 after 350 min [13].…”
Section: Introductionmentioning
confidence: 91%
“…By swelling analysis demonstrated that the synthetized hydrogel is not dependent of pH. Results showed that the obtained hydrogel reached a adsorption capacity of 172.41 mg g −1 after 350 min [13].…”
Section: Introductionmentioning
confidence: 91%
“…Chitosan and its precursor chitin are bioavailable polymers that come from the shells or skeletons of marine and nonmarine organisms [75]. They have been studied and used in a very large range of biomedical and nanobiotechnology applications because they have advantageous properties, such as nontoxicity, biocompatibility, biodegradability.…”
Section: Chitin/chitosanmentioning
confidence: 99%
“…Since, after 24 h, the results indicated a good adsorption capacity of the synthesized hydrogel, the tests were subsequently continued with the adsorption of diclofenac sodium (DS). This experiment will be described in Section 3.1.2 ( Figure 7 ) [ 97 ].…”
Section: Categories Of Chitosan-based Hydrogels For Water Purificatio...mentioning
confidence: 99%
“…The experiments were made at different pH values (pH 3, pH 7, and pH 9). The results showed that the swelling degree after 4 h is 83%, independent of pH values, in the limit of experimental errors [ 97 ]. The hydrogel showed an adsorption capacity (172.41 mg/g) at the highest amount of the adsorbent (200 mg) after 350 min.…”
Section: Categories Of Chitosan-based Hydrogels For Water Purificatio...mentioning
confidence: 99%
See 1 more Smart Citation